CHARACTERISTICS OF RETINOPATHY OF PREMATURITY IN MAKASSAR BETWEEN JANUARY 2020 AND DECEMBER 2022: Poster Presentation - Observational Study - Ophthalmologist - RAHMAH, MARLYANTI NUR; MUHIDDIN, HABIBAH S. (Majalah Oftalmologi Indonesia, 2023)
Introduction & Objectives : Introduction: Retinopathy of Prematurity (ROP) is one of the leading causes of irreversible visual impairment in infants, especially in premature infants. Preterm birth leads to incomplete development of retina that will cause ROP. ROP screening is an early strategy to prevent irreversible blindness in ROP. Objective: The purpose of this study was to describe the characteristics of ROP in Makassar between January 2020 and December 2022. Methods : A multi-center observational descriptive study at ten hospitals in Makassar. Results : The total patients in this study were 168 infants (336 eyes) included 53.25% male and 46.15% female. The incidence of ROP in Makassar between January 2020 and December 2022 was 14.87%. Most of the patients had history of preterm birth with gestational age ranged from 28 to 33 weeks and low birth weight less than 1500 gram in 50% patients. Majority of patients had history of oxygen therapy (77.98%), and other risk factors such as sepsis, twin birth, history of transfusion, or apnea. About 98.81% patients had bilateral ROP and 33.93% were diagnosed with stage 3 at first screening. Photocoagulation laser was done in 41 patients (24.40%). Conclusion : The ROP screening in Makassar had a good outcome in managing the premature infants, so they can be diagnosed and got treated earlier. A sustainable screening program is required to prevent the irreversible blindness due to ROP.